LINEAMENT STUDY OF THE SEMANGGOL FORMATION USING REMOTE SENSING TECHNIQUE - AZMAN, ALI IMRAN (2020)
Located in Kedah and northern Perak area, the Semanggol Formation was a continuous formation that was separated into three areas by sinistral strike-slip fault before igneous intrusion occurred in the adjacent areas of the formation. Research on the lineament mapping was done by a few researchers, however the mapping was not covered for the whole of the Semanggol Formation, especially in North Perak and lacking on lineament and geological boundary interpretation for estimating the displacement of the formation. This study aims to update the estimation of the displacement of the Semanggol Formation. Remote sensing data such as Landsat 5 TM, Landsat 7 ETM+ and Landsat 8 OLI, associated with digital elevation model (DEM) and drainage pattern were used to trace negative lineaments.